LEGAL UNIFICATION AND PLURALISM IN CUSTOMARY MARRIAGE REGISTRATION: LESSONS FROM THE BADUY INDIGENOUS COMMUNITY - Muhyidin Muhyidin; Budi Setyawan (Masalah-Masalah Hukum, 2025)
Marriage registration within the Baduy community reflects an inherent tension between customary law and state law, particularly within the framework of the Compilation of Islamic Law  in Indonesia. This study aims to analyze the differences in marriage registration practices between Baduy customary law and Islamic legal regulations in Indonesia, as well as to identify the social and legal implications arising from these differences. This research employs a qualitative approach using a socio-legal method. Data were collected through literature review, interviews with customary leaders, and field observations. The findings indicate that the Inner Baduy (Baduy Dalam) community continues to maintain a customary marriage system that does not require formal registration within the state administrative system. This practice is grounded in a strong adherence to customary norms, which are regarded as possessing high social legitimacy within the community. In contrast, the Outer Baduy (Baduy Luar) community has begun to demonstrate a degree of openness toward the national legal system by accepting administrative marriage registration. The area of Cicakal Girang serves as a point of compromise between customary law and state law, where marriage registration is carried out without entirely abandoning traditional values. Nevertheless, several differences remain evident in marital practices within the Baduy community, particularly in relation to arranged marriages, the prohibition of polygamy, and the mechanisms governing divorce. In this context, marriage registration in Cicakal Girang represents a practical accommodation between customary law and state law, although certain divergences persist in the implementation of marital norms. This study recommends the establishment of more intensive dialogue between the government and indigenous communities to bridge the gap between state law and customary law. An inclusive approach that is sensitive to local wisdom is essential in developing a more adaptive legal system. Such an approach would ensure the protection of the rights of indigenous peoples while preserving the cultural identity and traditions that remain central to the Baduy community.